Disease‐specific interactome alterations via epichaperomics: the case for Alzheimer's disease. (12th June 2021) - Ginsberg, Stephen D.; Neubert, Thomas A.; Sharma, Sahil; Digwal, Chander S.; Yan, Pengrong; Timbus, Calin; Wang, Tai; Chiosis, Gabriela
Abstract : The increasingly appreciated prevalence of complicated stressor‐to‐phenotype associations in human disease requires a greater understanding of how specific stressors affect systems or interactome properties. Many currently untreatable diseases arise due to variations in, and through a combination of, multiple stressors of genetic, epigenetic, and environmental nature. Unfortunately, how such stressors lead to a specific disease phenotype or inflict a vulnerability to some cells and tissues but not others remains largely unknown and unsatisfactorily addressed. Analysis of cell‐ and tissue‐specific interactome networks may shed light on organization of biological systems and subsequently to disease vulnerabilities. However, deriving human interactomes across different cell and disease contexts remains a challenge. To this end, this opinion article links stressor‐induced protein interactome network perturbations to the formation of pathologic scaffolds termed epichaperomes, revealing a viable and reproducible experimental solution to obtaining rigorous context‐dependent interactomes. This article presents our views on how a specialized 'omics platform called epichaperomics may complement and enhance the currently available conventional approaches and aid the scientific community in defining, understanding, and ultimately controlling interactome networks of complex diseases such as Alzheimer's disease. Ultimately, this approach may aid the transition from a limited single‐alteration perspective in disease to a comprehensive network‐based mindset, which we posit will result in precision medicine paradigms for disease diagnosis and treatment. Abstract : This opinion piece presents our view how understanding interactome networks of complex diseases such as Alzheimer's disease through epichaperomics may aid the transition from a limited single‐alteration perspective in disease to a comprehensive network‐based mindset. We posit a treatment paradigm may open and provide a previously unavailable precision medicine approach by understanding and targeting the interactome.